Pulmonary ventilation imaging in asthma and cystic fibrosis using oxygen‐enhanced 3D radial ultrashort echo time MRI. Issue 5 (31st October 2017) - Zha, Wei; Kruger, Stanley J.; Johnson, Kevin M.; Cadman, Robert V.; Bell, Laura C.; Liu, Fang; Hahn, Andrew D.; Evans, Michael D.; Nagle, Scott K.; Fain, Sean B.
Abstract : Background: A previous study demonstrated the feasibility of using 3D radial ultrashort echo time (UTE) oxygen‐enhanced MRI (UTE OE‐MRI) for functional imaging of healthy human lungs. The repeatability of quantitative measures from UTE OE‐MRI needs to be established prior to its application in clinical research. Purpose: To evaluate repeatability of obstructive patterns in asthma and cystic fibrosis (CF) with UTE OE‐MRI with isotropic spatial resolution and full chest coverage. Study Type: Volunteer and patient repeatability. Population: Eighteen human subjects (five asthma, six CF, and seven normal subjects). Field Strength/Sequence: Respiratory‐gated free‐breathing 3D radial UTE (80 μs) sequence at 1.5T. Assessment: Two 3D radial UTE volumes were acquired sequentially under normoxic and hyperoxic conditions. A subset of subjects underwent repeat acquisitions on either the same day or ≤15 days apart. Asthma and CF subjects also underwent spirometry. A workflow including deformable registration and retrospective lung density correction was used to compute 3D isotropic percent signal enhancement (PSE) maps. Median PSE (MPSE) and ventilation defect percent (VDP) of the lung were measured from the PSE map. Statistical Tests: The relations between MPSE, VDP, and spirometric measures were assessed using Spearman correlations. The test–retest repeatability was evaluated using Bland–Altman analysis and intraclass correlation coefficients (ICC). Results: Ventilation measures in normal subjects (MPSE = 8.0%, VDP = 3.3%) were significantly different from those in asthma (MPSE = 6.0%, P  = 0.042; VDP = 21.7%, P  = 0.018) and CF group (MPSE = 4.5%, P  = 0.0006; VDP = 27.2%, P  = 0.002). MPSE correlated significantly with forced expiratory lung volume in 1 second percent predicted ( ρ  = 0.72, P  = 0.017). The ICC of the test–retest VDP and MPSE were both ≥0.90. In all subject groups, an anterior/posterior gradient was observed with higher MPSE and lower VDP in the posterior compared to anterior regions ( P ≤ 0.0021 for all comparisons). Data Conclusion: 3D radial UTE OE‐MRI supports quantitative differentiation of diseased vs. healthy lungs using either whole lung VDP or MPSE with excellent test–retest repeatability. Level of Evidence : 2 Technical Efficacy : Stage 1 J. Magn. Reson. Imaging 2018;47:1287–1297.